Private associations and Jewish communities in the Hellenistic and Roman cities - Eckhardt, Benedikt (The Medieval Franciscans, 2019)
In Private Associations and Jewish Communities in the Hellenistic and Roman Cities, Benedikt Eckhardt brings together a group of experts to investigate a problem of historical categorization. Traditionally, scholars have either presupposed that Jewish groups were "Greco-Roman Associations" like others or have treated them in isolation from other groups. Attempts to begin a cross-disciplinary dialogue about the presuppositions and ultimate aims of the respective approaches have shown that much preliminary work on categories is necessary. This book explores the methodological dividing lines, based on the common-sense assumption that different questions require different solutions. Re-introducing historical differentiation into a field that has been dominated by abstractions, it provides the debate with a new foundation. Case studies highlight the problems and advantages of different approaches.